Advances in thickness measurements and dynamic visualization of the tear film using non-invasive optical approaches. (May 2017) - Bai, Yuqiang; Nichols, Jason J.
Abstract: The thickness of tear film has been investigated under both invasive and non-invasive methods. While invasive methods are largely historical, more recent noninvasive methods are generally based on optical approaches that provide accurate, precise, and rapid measures. Optical microscopy, interferometry, and optical coherence tomography (OCT) have been developed to characterize the thickness of tear film or certain aspects of the tear film (e.g., the lipid layer). This review provides an in-depth overview on contemporary optical techniques used in studying the tear film, including both advantages and limitations of these approaches. It is anticipated that further developments of high-resolution OCT and other interferometric methods will enable a more accurate and precise measurement of the thickness of the tear film and its related dynamic properties. Highlights: Achievements of contemporary optical techniques and related limitations are reviewed. Ultra-high resolution OCT emerged as one relatively new techniques. Further development of OCT with other interferometric or microscopic principles are discussed.